Pengaruh model pembelajaran self regulated learning (srl) terhadap keterampilan berpikir kritis pada pembelajaran ipa ditinjau dari internal locus of control - Nanda Cossin Nawa Salsabiela; Roy Ardiansyah; Matsuri Matsuri (Didaktika Dwija Indria, 2025)
The aim of this study is to know the impact of the Learning Model Self-Regulated Learning (SRL) on Critical Thinking Skills (KBK) on learning IPA reviewed from the Internal Locus of Control. (ILC). This type of research is quasi-experimental. The sample of this study was 88 pupils, of which 46 pupils were grouped into experimental classes for treatment using the SRL learning model and 42 pupils treated using the Direct Instruction learning model. (DI). Data collection techniques use tests and scales. The data was then analyzed using the Anava Two Way Hypothesis Testing Technique and the Schaffe Advanced Testing Method. The results of the study showed that there was an influence between the SRL learning model and the DI learning model on pupils with low, medium, and high ILC against KBK on IPA learning with a significance level of 0,000 > 0,05. Students with a high ILC have a better KBK score (87,46) when given the SRL learning model. While students with low internal locus have a better and responsive KBK score (67,86) when given with the DI learning model. However, overall learners with low, medium, and high ILCs were better when given the SRL learning model with a marginal rate of 73.41.